Acaricidal Activity of Essential Oils from Tulsi (Ocimum basilicum), Bach (Acorus calamus) and Mint (Mentha arvensis) Against Rhipicephalus sanguineus (Latreille) - Manzoor, Farkhanda; Fazal, Sabiha; Munir, Neelma; Naz, Shugufta; Khalid, Anam (Asian Journal of Chemistry, 2013)
The present study was carried out to find the acaricidal efficacy of three essential oils, Acorus calamus, Mentha arvensis and Ocimum basilicum against most widely found dog tick, Rhipicephalus sanguineus. The oils were tested at 1:15 (v/v; oil: ethanol, 66.6 μL/mL), 1:30 (33.3 μL/mL), 1:45 (22.2 μL/mL), 1:60 (16.6 μL/mL) and 1:75 (13.3 μL/mL) concentrations. The mortality was observed after every 15 min interval, within 2 h. All tested oils showed significant results against Rhipicephalus sanguineus. The highest acaracidal activity (100 % mortality) was observed with Ocimum basilicum oil at 1:15 (66.6 μL/mL) with LC50 value as 32.31 μL/mL. 100 % mortality was obtained for concentrations (66.6, 33.3, 22.2, 16.6 μL/mL) at 60 min for Ocimum basilicum. Acorus calamus showed medium acaricidal activity and 100 % mortality was obtained for concentrations (66.6, 33.3, 22.2 μL/mL) at 1 h with LC50 value as 13.461 μL/mL. Mentha arvensis showed least acaricidal activity with 22.2, 16.6 and 13.3 μL/mL and 100 % mortality for concentrations (66.6, 33.3 μL/mL) was observed at 60 min with LC50 value as 19.71 μL/mL. In vivo experimental concentration of Ocimum basilicum; 1:5 (w/w; oil: pure petroleum jelly) and 1:10 (w/w oil: pure petroleum jelly) showed 100 % mortality after 1 and 2 h, respectively. It was concluded that Ocimum basilicum is a promising candidate for controlling Rhipicephalus sanguineus.